Molecular identification and antibiotic susceptibility patterns of bacterial isolates from urine samples of African buffalo, eland and cattle - Harry Asena Musonye; Ezekiel Mugendi Njeru; Ahmed Hassanali; Lydia Mali Langata; James Nonoh (Hasanuddin University, 2021)
Presence of antibiotic resistant bacteria in natural environment is an escalating risk of serious implication on human and animal health. Livestock and wildlife have been long recognized as reservoirs for antibiotic resistant bacteria. Nonetheless, there is limited knowledge regarding the potential of livestock and wildlife urine to act as transmission corridor for the spread of antibiotic resistant bacteria. The present study aimed at evaluating antibiotic susceptibility patterns and molecular identification of bacteria isolated from livestock and wildlife urine samples. A total of 19 different bacteria isolated from urine samples of African buffalo, eland and cattle were subjected to antibiotic susceptibility test. The isolates showed diverse susceptibility patterns against co-trimoxazole, tetracycline, amoxycillin, ciprofloxacin, streptomycin, nalidixic acid, chloramphenicol and gentamicin. Of the tested isolates, 73.7 % were exhibited resistance while 31.6 % were intermediate to the range of antibiotics tested. High resistance prevalence to amoxicillin (58%), tetracycline (26 %) and co-trimoxazole (11%) by the tested bacteria was observed. This study reveals the bacteria associated with African buffalo, eland and cattle urine as potential candidates for antibiotic resistance. This information demonstrates the need for measures to be adopted to limit the presence of antibiotic resistant bacteria in wildlife and livestock reservoirs.